Study of Fishermen's Satisfaction Level With E-Logbook Services at the Ocean Fishing Port (OFP) Bitung, North Sulawesi - Erna; Mukhlisa A Ghaffar; Nurfadillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bitung Ocean Fishing Port is one of the type A ports in Indonesia. Some of the services provided are available at the Syahbandar OFP Bitung office. The quality of service should be a reference for other types of fishing ports. The purpose of this study is to analyze the level of fishermen's satisfaction and service attributes that need to be improved in the e-logbook service at the Ocean Fishing Port (OFP) Bitung, North Sulawesi. This research was conducted by taking data through surveys directly with the questionnaire distribution method. The analysis methods used are Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of the study obtained, for the value of the level of agent satisfaction with fishing e-logbook services include 5 variables, namely reliability 81.32%, responsiveness 84.44%, certainty 83.23%, empathy 89.04%, physical facilities 86.24% with a total overall CSI value of 84.85%. This value shows that fishermen have a perception that the service of the e logbook is very satisfying. Meanwhile, the service attribute a that must be improved in performance is problem responsiveness. Thus, OFP Bitung will be able to provide the best service according to the expectations of users of the e logbook service